Wee Willie Winkie runs through the town ... to count the many children reading library books / Cleo Sara. - Sara, Cleo, artist (Chicago : Illinois WPA Art Project, 1940)
Poster promoting the use of libraries by children, showing a child in pajamas and slippers running through a village at night.